Leveraging Faculty Development and Assessment Efforts: A Case Study - Ryan Chung (Academic Chairpersons Conference Proceedings, 2018)
While assessment is critical for enhancement of student learning, it is rarely viewed explicitly as an essential aspect of faculty development. The presenter will share stories and experiences in developing and implementing assessment initiatives as faculty development, leading to strong culture of assessment at a research one institution.
Keywords: Assessment; Higher Education; Administration; Education Leadership; Faculty Development